Cost management: modelling asymmetric cost behaviour - Yakymova, Larysa (The Academy of Management and Administration in Opole, 2021)
The traditional assumption in cost accounting and management is that variable costs move in proportion to the activity volume (sales revenue). However, recent empirical studies provide evidence that the cost response to decreased activity may be less or greater than the cost response to increased activity. Using the ABJ model, we examine the behaviour of the cost of goods sold (COGS), administrative costs, and selling costs in municipal environmental and water utilities from Ukraine for the period 2012-2019. We find strong evidence that the type and degree of cost asymmetry differs across cost items and types of economic activity. The study found that COGS is sticky in environmental enterprises as it grows an average of .818% with a 1% increase in net sales revenue, and only declines .087% with a 1% decrease in net sales revenue. Whereas in water utilities, COGS exhibits anti-sticky behaviour as it increases on average .280% with a 1% increase in net sales revenue, but decreases 1.512% with a 1% decrease in net sales revenue. Administrative costs have shown similar behaviour, but the total selling, administrative costs, and other operating costs demonstrate statistically insignificant sticky behaviour in both types of enterprises. As the main reason for cost stickiness, we support managerial motivation underlying resource adjustments in the face of fluctuations in activity volumes.
Keywords: stickiness costs, cost of goods sold, administrative costs, ABJ model, municipal enterprises